2018
DOI: 10.21307/pjm-2018-041
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Microbiota and Fatty Acids in the Faeces of Overweight and Obese Children

Abstract: The growing number of children with overweight and obesity constitutes a major health problem of the modern world and it has been suggested that intestinal microbiota may influence energy intake from food. The objectives of this study were to determine quantity and proportions of dominant genera of Bacteroides, Prevotella (phylum Bacteroidetes); Clostridium, Lactobacillus (phylum Firmicutes) and Bifido bacterium (phylum Actinobacteria) in the intestines and to determine the content of short-chain fatty acids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
1
38
0
5
Order By: Relevance
“…After we further examined the 29 identified articles, 22 articles were excluded (Supplementary Table S2). Finally, we identified seven articles that met the inclusion criteria [8,9,10,11,13,24,25]. The overall quality of the studies averaged eight stars (range, 7–9) on a scale from zero to nine stars (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After we further examined the 29 identified articles, 22 articles were excluded (Supplementary Table S2). Finally, we identified seven articles that met the inclusion criteria [8,9,10,11,13,24,25]. The overall quality of the studies averaged eight stars (range, 7–9) on a scale from zero to nine stars (Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…However, in human studies, there have been mixed results regarding the relationship between SCFAs and obesity. For example, some studies have reported a positive correlation between fecal SCFA concentrations and obesity [8,9,10]; however, others have reported a negative relationship between SCFA levels and obesity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Promising preliminary studies show that SCFAs may play a role in energy metabolism and stimulate secretions of hormones that enhance food absorption [ 130 ]. However, the role of SCFAs in obesity still remains controversial due to mixed results from clinical studies [ 131 , 132 ]. On the other hand, in developing countries, malnutrition affects many children that become predisposed to infections [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet established whether the changes in certain bacterial populations could be strong biomarkers of obesity or T2DM. While the Firmicutes to Bacteroides ratio in the gut may be higher during obesity but reduced in lean people [102][103][104][105], a systematic review of available literature indicates that the differences do not represent a consistent feature for distinguishing lean individuals from obese ones [106]. Interestingly, some human studies showed no changes in the Bacteroidetes/Firmicutes ratio between fecal samples of lean and obese subjects [107][108][109][110].…”
Section: Obesity and Type-2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%